Effects of an 8-week Tai Chi intervention on attention quality in university students - Lyu, Chengying; Shen, Qiqi; Liu, Yutong; Hou, Jinmei; Xia, Tong; Chai, Qiuyue; Song, Anqi; Xiao, Yang; Zhang, Qiongyue; Li, Jiaqi; Cui, Lei; Yin, Hengchan (The Journal of the International Society of Chinese Health Practices, 2025)
Abstract: Objective: Attention quality—comprising concentration assignment, span, stability, and transference—is critical to cognitive function and academic performance. University students face increasing cognitive demands, highlighting the need for effective attention-enhancing strategies. Tai Chi, a traditional Chinese mind-body exercise, emphasizes breath regulation, mental focus, and coordinated movement, and may benefit attention regulation. This study examined the effects of an 8-week Tai Chi intervention on the multidimensional structure of attention quality. Methods: Ninety undergraduates wererandomly assigned to a Tai Chi group (n = 29), a brisk walking group (n = 30), or a control group (n = 31). Both exercise groups engaged in moderate-intensity activity three times weekly for 60 minutes per session over eight weeks. A 3 (Group) × 2 (Time: Pre, Post) mixed factorial design was used. Four standardized concentration tests assessed the four attention dimensions, each recording total and correct responses to reflect processing efficiency and accuracy. Data were analyzed using repeated-measures ANOVA. Results: Significant time effects were found across all dimensions, indicating improvement from pre- to post-test in all groups. For concentration assignment, a significant time × group interaction was observed for both total and correct responses, with the Tai Chi group showing marginally greater improvement than the brisk walking group (p = 0.051). In the span dimension, a marginal interaction was found for correct responses (p = 0.065), although no significant group differences were identified. For both stability and transference, only main effects of time were observed, with no group or interaction effects. Conclusion: Both Tai Chiand brisk walking improved attention quality after eight weeks, with Tai Chi showing a slight advantage in enhancing concentration assignment. Its coordinated focus on breath, intention, and movement may contribute to attentional benefits. However, no clear superiority was found in other dimensions. These findings suggest Tai Chi is a promising non-pharmacological intervention for supporting attention regulation in college students, but further investigation is needed to clarify its dimension-specific effects and mechanisms.